Total Hip Arthroplasty Stems and Femur Strain During Implant Insertion: A Biomechanical Study of Single Taper, Double Taper, and Collared Monolithic Stems - Barrett Bruno Torre; Jordan Andre Bauer; Ian Wellington; Tannaz Sedghi; Dillon Neumann; Adam Lindsay; Olga Solovyova (Orthopaedic Surgery)
ABSTRACT Objective In total hip arthroplasty (THA), intraoperative periprosthetic femoral fracture (IOPFF) is a significant concern, often occurring during femoral canal instrumentation and stem implantation due to proximal femur strain. However, the impact of different stem designs on this strain remains unclear. This study conducted a biomechanical analysis comparing strain patterns on the proximal femur during the implantation of three stem types: single taper, double taper, and collared stems. This study aims to explore if there is a difference in strain patterns placed on the proximal femur during the implantation of three different stem types: single taper, double taper, and collared stems? Methods There were 24 cadaveric femurs randomly assigned to three groups based on implant geometry: Smith and Nephew anthology (single taper), synergy (double taper), and polar (collared) stems. Strain gauges were placed on the proximal femur to measure strain during implantation in both horizontal and vertical directions. Peak strain, the difference between maximum strain at final impaction and baseline, was recorded. The Kruskal–Wallis test compared peak strain between stem designs. Results At the medial proximal femur, collared stems produced compressive strain (−276) in the horizontal vector, differing significantly from the tensile strain generated by single (41, p = 0.009) and double taper stems (218.5, p = 0.003). No significant strain difference existed between single and double taper stems at the medial proximal femur. At the lateral proximal femur, double taper stem impaction resulted in compressive strain (−69), significantly differing from the tensile strain produced by single taper (221, p = 0.024) and collared stem impaction (462, p = 0.009). No strain differences were observed in other tested areas. Conclusion This study highlights distinct strain patterns at the medial and lateral proximal femur depending on the stem type. Collared stems induce compressive strain at the medial proximal femur, while double taper stems result in compressive strain at the lateral proximal femur. Understanding these differences may help reduce IOPFF risk in THA procedures. Based on these findings, the use of collard stems would be preferable over single or double taper stems in elderly patients with suboptimal bone quality, as it reduces strain on the medial cortex and improves immediate stability.